The arrival of the King: the shape and story of Psalms 15-24 - Quinn, Carissa (Studies in Scripture and Biblical Theology Series, 2023)
"The suffering psalmist and chosen king The Psalter evinces meaningful arrangement. When psalms are read with attentiveness to their textual context, striking connections emerge. In The Arrival of the King: The Shape and Story of Psalms 15-24, Carissa Quinn approaches these psalms as a compositional unity. When read as a unit, Psalms 15-24 tell the story of God's kingdom, established through the suffering and deliverance of his Davidic king. Quinn interprets Psalms 15-24 as a sequence and a chiasm, revealing provocative links in adjacent and parallel psalms. These psalms have a sense of progress, beginning with the question of who may ascend the holy hill and culminating in the divine king's own ascent. They also display recursion, as themes in one psalm are developed in its chiastic parallel. At the peak of the chiasm is Psalm 19, where the king praises God's creation and Torah and prays for righteousness. The Arrival of the King establishes and explores the rewards of approaching the Psalms as a carefully arranged literary work"--